Women with mechanical neck pain exhibit increased activation of their superficial neck extensors when performing the cranio-cervical flexion test. (October 2020) - Bonilla-Barba, Laura; Florencio, Lidiane Lima; Rodríguez-Jiménez, Jorge; Falla, Deborah; Fernández-de-las-Peñas, César; Ortega-Santiago, Ricardo
Abstract: Background: Several studies have analysed the activity of superficial neck flexors, but the activity of neck extensors has been less investigated in patients with neck pain Objectives: 1, to investigate the differences in the activation of superficial neck flexor and extensor musculature during the cranio-cervical flexion test (CCFT) in women with mechanical chronic neck pain when compared to asymptomatic women; 2, to investigate the correlation between neck muscle activity and the clinical features of neck pain Design: Cross-sectional Methods: Surface electromyography was recorded bilaterally from the sternocleidomastoid, anterior scalene, splenius capitis, and upper trapezius muscles of 30 women with mechanical chronic neck pain and 30 asymptomatic women as they performed the CCFT. Comparisons of the normalized root mean square between both groups were conducted with 2x5 ANCOVA with task level as the within-subjects variable, group as the between-subjects variable, and pain related-disability as a co-variate Results: Women with mechanical neck pain exhibited increased activity of superficial neck flexors (sternocleidomastoid: F = 14.448, P < 0.001; anterior scalene: F = 21.693, P < 0.001) and superficial neck extensors (splenius capitis: F = 4.692, P < 0.001; upper trapezius: F = 4.245, P < 0.001) as compared to asymptomatic women. Higher pain related-disability was associated with more electrical activity of the anterior scalene and upper trapezius muscles during the CCFT Conclusions: Women with mechanical chronic neck pain exhibit an increased activity of their superficial neck flexors and superficial neck extensors during a low-load task such as CCFT when compared to asymptomatic pain-free women. Our results should be considered when designing therapeutic exercise programs for this population. Highlights: Chronic neck pain presents increased activity of neck extensors during CCFT. Increased activity of neck extensors and superficial flexors are proportional. Greater scalene and upper trapezius activity correlate with worse disability.